2021
DOI: 10.1111/jfd.13346
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis provides insight into the key proteins as potential targets underlying the effect of malachite green against Ichthyophthirius multifiliis

Abstract: Target identification is important for drug discovery. Unfortunately, no drug targets have been found in Ichthyophthirius multifiliis until now and further limited development of the novel drug for Ichthyophthiriasis. In this study, an iTRAQ‐based quantitative proteomic analysis was used to find the target of malachite green (MG), exhibiting greater efficacy than the existing drugs, against I. multifiliis trophonts in situ. We also verified the proteomic results by RT‐qPCR, TEM and cell apoptosis assay. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…Furthermore, our TEM results demonstrated that berberine treatment resulted in the damage of organelles and cytomembranes, reflected in the reduction in the number of ribosomes, the rupturing of the inner membrane of mitochondria, and mitochondrial swelling. This is similar to the results of Qu′s and Ruider′s studies [ 7 , 32 ]. Ribosomes are critical in protein production in all cells, and the I. multifiliis is no exception.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, our TEM results demonstrated that berberine treatment resulted in the damage of organelles and cytomembranes, reflected in the reduction in the number of ribosomes, the rupturing of the inner membrane of mitochondria, and mitochondrial swelling. This is similar to the results of Qu′s and Ruider′s studies [ 7 , 32 ]. Ribosomes are critical in protein production in all cells, and the I. multifiliis is no exception.…”
Section: Discussionsupporting
confidence: 92%
“…Our results suggested that berberine causes structural alterations in parasite cells, particularly severe disruption to the inner membrane of mitochondria. These effects are similar to those achieved by the treatment with malachite green [ 7 , 32 ] and 10-gingerol [ 39 ]. In Fu’s study, 10-gingerol reduced ATP ase activities, leading to the accumulation of free radicals, which further led to the destruction of cell membranes and organelles.…”
Section: Discussionsupporting
confidence: 80%
“…Specifically, the protein processing in endoplasmic reticulum pathways might be attributed to the oxidative and endoplasmic reticulum stresses, which could initiate apoptosis as an adaptive mechanism for oxidative stress in crabs . As previously discussed, the ribosome is essential for protein synthesis in cells . Oxidative phosphorylation plays a crucial role in the oxidative stress in mitochondria and apoptosis in cells .…”
Section: Resultsmentioning
confidence: 99%
“…76 As previously discussed, the ribosome is essential for protein synthesis in cells. 77 Oxidative phosphorylation plays a crucial role in the oxidative stress in mitochondria and apoptosis in cells. 78 Additionally, the TCA cycle enhanced the immune response in crabs, indicating the activation of immune and antioxidation functions in crabs during the first stage of transportation.…”
Section: Cardiac and Respiratory Pathwaysmentioning
confidence: 99%
“…In recent years, apoptosis has provided a new treatment for many diseases, such as inflammation, cancer, leishmaniasis, malaria, and toxoplasmosis [ 7 14 ]. The apoptosis-like death pathway has also been found in many protozoa, such as Leishmania, Plasmodium falciparum , Tetrahymena thermophila , Trypanosoma cruzi , Blastocystis hominis , Toxoplasma gondii , and Ichthyophthirius multifiliis [ 12 21 ], providing a new way to treat parasitic diseases. Many apoptosis-related genes of C. irritans have been found via transcriptome analysis [ 22 26 ], which indicates that C. irritans might have an apoptosis-like death pathway.…”
Section: Introductionmentioning
confidence: 99%